GAHARU INOCULATION TRAINING FOR COMMUNITIES NEAR THE PT. ARUTMIN INDONESIA SENAKIN MINE IN SOUTH KALIMANTAN - Rezekiah, Arfa Agustina; Fithria, Abdi; Guspianur, Selimi; Prakoso, Yudo; Alvhian Noor, Andi; Firdaus, Noor; Ferry, Ferry; Gunawan, Gunawan; Fajar, Fajar; Syahrani, Syahrani; Jarkasi, Jarkasi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Indonesia is a country rich in forest products. One of which is Gaharu, a treeless forest product with high economic value for the perfume, incense, and pharmaceutical industries. Gaharu in Indonesia comes from gaharu trees that are infected with bacteria so that the result is gaharu. Many aloes grow in Indonesia, one of which is in the settlement around the PT Arutmin Indonesia mine. In this case, the community needs science and technology to optimally utilize the abundant gaharu in their area. The purpose of this service is to provide science and technology as well as additional skills in utilizing gaharu effectively and quickly. The community was very enthusiastic in this service activity by actively participating in activities both from socialization to the practice of making gaharu sapwood inoculation. The manufacture of gaharu sapwood by inoculation is carried out using a drilling machine by wounding the trunk of the gaharu tree and then the wound is given bacteria that can make gaharu produce resin that is useful and of high selling value.